دراسة النمو والإزهار والإثمار لدورات النمو السنوية عند صنف البرتقال أبو سرة - ديب علي; نبيعه عمار (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة في قرية ستخيرس التابعة لريف محافظة اللاذقية خلال عامي ((2018,2017 ضمن بستان حمضيات يحوي (55) شجرة برتقال صنف أبو سرة بعمر (15) سنة و مطعمة على الأصل النارنج . بهدف إيجاد العلاقات القائمة بين توزع دورات النمو السنوية على السطح المنتج وبين كمية الإنتاج و جودة الثمار، أجريت التجربة كتجربة عاملية بأربع قطع تجريبية موزعة على الجهات الأربع للبستان (قطعة في كل جهة ) وبمعدل (3) أشجار للقطعة الواحدة وتمثل كل شجرة مكرر واحد وتشمل التجربة عاملين هما الطبقات ( التغير في الإرتفاع) ودورات النمو السنوية (ربيعية – صيفية – خريفية), و خلصت الدراسة إلى النتائج الآتية : تفوق دورة النمو الربيعية على دورتي النمو الصيفية والخريفية في الطبقات الثلاث للتاج بعدد الأوراق وعدد النموات الخضرية ,بينما تفوقت دورة النمو الخريفية في الطبقة الثانية بنسبة العقد والحمل. The study was carried out in the village of Setkhiris belonging to the countryside of Lattakia Governorate during (2017,2018) within the citrus field containing (55)orange trees of washington navel the age of 15 years old and grafted on citrus aurantium root stock, to study of the relationships between the distribution of the seasonal growth cycles on the productive surface and the quantity of production and the quality of the fruits The experiment was carried out as a global experiment with four experimental plots distributed on the four sides of the field (one piece in each area) and (3) trees for per piece. Each tree represents one replicator, The experiment includes two factors (the change in height) and the seasonal growth cycles (Spring - summer – autumn), The result of this study showed the following: The spring growth cycle surpassed the summer and autumn growth cycles in the three layers of the crown with the number of leaves and the number of vegetative growths, exceeding the autumn growth cycle in the second layer by contract.